(3GdTQcI GdegfjI PGJ GdTcd GdJLGQi hGKQ GdGadGS YdjgG ai GdbGfhf GdaQfSi hGdbGfhf GdchjJi (B: s (3OQGSI bGfhfjI ebGQfI (B/ s - (3jhSa eWdb eMeO GdeWhWMs; (3SejMI GdbdjhHi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3dbO JfGhdJ GdQSGdI UhQ eeGQSI Gdegf GdMQI GdJi JNVY dfXGe JTQjYi Gh dGFMi hPdc ShGA ai GWGQ GdTQcGJ GdegfjI GYeGdG ddbGfhf GdaQfSi GdUGOQ ai (B29 (3fhaeHQ (B1966 (3HTCf GdTQcGJ GdeOfjI GdegfjI Gh ai GWGQ GdTQcGJ GdJLGQjI JWHjbG ddbGfhf GdaQfSi GdUGOQ ai (B31 (3OjSeHQ (B1990 (3hGdeYOd YGe (B2001 (3HTCf eeGQSI Gdegf GdMQI GdJi JNVY dfXGe JTQjYi Gh dGFMi ai Tcd GdTQcGJ PGJ GdeSFhdjI GdeMOhOIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2008s
(3HHdjhLQGajG(B: (3UaMGJ (B503-514s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdegfI GdMQIs; (3GdTQcI GdeOfjI GdegfjIs; (3GdTQcI GdegfjI PGJ GdTcd GdJLGQis; (3GdTQhW GdehVhYjI dJCSjS GdTQcGJ GdegfjI GdJLGQjIs; (3GdTQhW GdTcdjI dJCSjS GdTQcGJ GdegfjI GdJLGQjIs; (3CMcGe GdTQcGJ GdegfjI aj bGfhf GdTQcGJ GdchjJjs; (3TQcI GdTNU GdhGMO aj eLGd Gdegf GdMQIs; (3JWHjb GdJShjI GdhOjI Ydi GdTQcGJ GdegfjIs; (3ETgGQ EadGS GdTQcGJ aj GdJTQjY GdchjJjs; (3ETgGQ EadGS GdTQcGA GdeJVGefjf aj GdJTQjY GdchjJjs; (3JWHjb GdJbhje GdbVGFj Ydi GdTQcGJ GdegfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs